Variasi Musiman Sea Level Anomaly di Wilayah Perairan Indonesia - Haryo, Julis Dani; Lizalidiawati, Lizalidiawati; Irkhos, Irkhos; Suhendra, Suhendra (JURNAL ENGGANO, 2024)
Indonesia's territory is located between two vast oceans, namely the Pacific and Indian Oceans as well as the two continents of Australia and the continent of Asia. As a result, Indonesia's regional climate is directly influenced by these geographical conditions. As is known, Indonesia experiences the Northwest Monsoon and Southeast Monsoon. The seasonal variations that occur include part of the aim of this research, namely to identify seasonal variations in sea surface anomalies (SLA) in three regions of Indonesia representing western, central and eastern waters using altimetry satellite image data. The coordinates of these three areas, namely, represent parts of the West Sumatra Sea (1°S – 3°S, 95°E – 100°E), Makassar Strait (5°S- 8°S, 119°E- 25°E), and the Banda Sea (5°S – 8°S, 125°E – 109°E). The data used for 30 years (1993-2022) is in the form of monthly average SLA data and processed using Panoply software to display the SLA distribution in each area as well as the SLA Time Series in the three regions. The research results show that the highest sea level rise occurred in area A (Western waters of Sumatra) with an SLA of 1.4 m with a rate of increase ranging from 0.5-1.4 m/year. In area B (Banda Sea), the SLA obtained is 1.2 m with an increase rate ranging from 0.7-1.2 m/year. Meanwhile in Area C (Makassar Strait) it is 1.3 m with an increase rate ranging from 0.7-1.3 m/year. Keywords: Sea Surfalce Height, Season variation, west, east, and middle region.